Dielectric and ferroelectric hysteresis properties of 1-3 lead magnesium niobate-lead titanate ceramic/Portland cement composites - Chaipanich,A. (Elsevier Limited, 2015)
In this work, lead magnesium niobate-lead titanate (PMN-PT) ceramic was cut and filled with Portland cement (PC) to produce 1-3 connectivity PMN-PT/PC composites. Dielectric and ferroelectric hysteresis properties of these composites with PMN-PT ceramic volume content of 60% were investigated. Room temperature dielectric constant (ε r) at 1 kHz of the PMN-PT/PC composite was found to be ≈1500. At higher frequency (20 kHz), the dielectric constant was reduced to the value of ≈1300. Ferroelectric (polarization-electric field) hysteresis loops at 10-90 Hz and varying electric field were measured. The "instantaneous" remnant polarization (P ir) at 50 Hz and at the electric field of 7 kV/cm of the PMN-PT/PC composite was found to be ≈10 μC/cm 2. These values of 1-3 composites therefore are promising when compared to previous results of composites at similar conditions. © 2011 Elsevier Ltd and Techna Group S.r.l.